Methodic approaches to the evaluation of the health of junior schoolchildren - Ye. A. Afanasyev; V. N. Vasilyev; Yu. V. Tyerentyeva; I. A. Sennikova (Бюллетень сибирской медицины)
The results of investigation of adaptive properties at 577 children of junior school age (7—9 years old) are presented in the paper. Rise of physical growth, physical health index and adaptation level up to the 9 years has been revealed. The period of the least adaptability at girls (8 years old) has been determined. The sexual differences of the determined factors at the age of 8 and 9 years have been marked.